The Effect Of Peanut Ball Use On The Duration Of Active Phase I Labor In Women In Labor At Majenang General Hospital In 2024 - Fifin Maya Kumala Mukti; Meti Widiya Lestari; Dita Eka Mardiani (Media Informasi, 2025)
Prolonged labor is one of the complications in childbirth that can lead to increased mortality and morbidity in mothers and fetuses. The incidence of prolonged labor remains high at Majenang General Hospital. One non-pharmacological method that can be used is the use of a peanut ball. Objective: To determine the effect of using a peanut ball on the duration of labor.  Method: This study used a quasi-experimental design with a post-test only control group design. The sampling technique used was total sampling, dividing the participants into two groups: a control group of 16 respondents and an intervention group of 16 respondents. Data analysis was performed using an independent samples t-test. Results: The results of this study showed a significant difference in the average duration of the first stage of active labor between the two groups (p < 0.05).